Complications associated with continuous renal replacement therapy. Issue 6 (7th April 2021) - Kovvuru, Karthik; Velez, Juan C. Q.
Abstract: With the evolution of standardized replacement fluids, newer machines, and high flux membranes, continuous renal replacement therapy (CRRT) has made remarkable progress in the field of extracorporeal therapies. CRRT is the preferred dialytic modality for patients in intensive care unit setting (ICU). Standardized protocols are implemented by many institutions to avoid errors and ensure patient safety. However, complications related to CRRT are not uncommon. Understanding CRRT operations is essential to analyze the complications and further assist in developing measures to mitigate the risk. Overview of CRRT complications and potential preventive strategies are discussed in the current review.